Synthetic human beta-globin 5'HS2 constructs function as locus control regions only in multicopy transgene concatamers. - Ellis, J (1993)
Transgenes linked to the beta-globin locus control region (LCR) are transcribed in a copy-dependent manner that is independent of the integration site. It has previously been shown that the LCR 5'HS2 region does not require its NF-E2 dimer binding site for LCR activity. In this paper we analyse synthetic 5'HS2 core constructs containing point mutations in the other factor binding sites 3' of the NF-E2 dimer site. The results show that 5'HS2 core is a partially active LCR that functions in a concatamer of at least two copies but not when present as a single copy in transgenic mice and that no single binding site within 5'HS2 is required for position-independent expression. In addition, the H-BP factor is identical to upstream stimulatory factor (USF) and full enhancement levels by 5'HS2 core in MEL cells require a combination of all the factor binding sites. We suggest that 5'HS2 cores in a concatamer interact with each other to establish an area of open chromatin and that this process may be the basis of LCR function.